Ocular diseases in patients with rheumatic diseases - Ausayakhun S. (2014)
To study the distribution of ocular involvement among persons with rheumatic disease, a cross-sectional survey was performed in 224 patients attending the Division of Rheumatology, Department of Medicine, Maharaj Nakorn Chiang Mai Hospital. Of these patients, 102 presented with rheumatoid arthritis, 74 systemic lupus erythematosus, 39 systemic sclerosis, 6 mixed connective tissue disease, 2 polymyositis and 1 juvenile rheumatoid arthritis. It was found that the ocular involvement probably related to diseases including dry eye (19.9%) and uveitis (0.4%), The ocular involvement was presumably related to treatment including retinopathy (7.6%), cataract (6.3%), and glaucoma (0.9%). Rapid recognition of these complications would lead to early and appropriate management, which would prevent their sequelae.